2022
DOI: 10.1186/s13017-022-00404-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating necrotizing soft tissue infections from cellulitis by soft tissue infectious fluid analysis: a pilot study

Abstract: Background We conducted this study to evaluate the characteristics of the infectious fluid in soft tissue infection and investigate the utility of the biochemical tests and Gram stain smear of the infectious fluid in distinguishing necrotizing soft tissue infection (NSTI) from cellulitis. Methods This retrospective cohort study was conducted in a tertiary care hospital in Taiwan. From April 2019 to October 2020, patients who were clinically suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…There were studies considered liver cirrhosis as risk factor with increased mortality among NSTI patients [ 9 , 26 29 ]. Previous study had demonstrated that hyperlactatemia is significantly associated with in-hospital mortality in NSTI patients, even after adjusting for acidosis [ 30 , 31 ]. The result was similar in the present study, even in V. vulnificus infection.…”
Section: Discussionmentioning
confidence: 99%
“…There were studies considered liver cirrhosis as risk factor with increased mortality among NSTI patients [ 9 , 26 29 ]. Previous study had demonstrated that hyperlactatemia is significantly associated with in-hospital mortality in NSTI patients, even after adjusting for acidosis [ 30 , 31 ]. The result was similar in the present study, even in V. vulnificus infection.…”
Section: Discussionmentioning
confidence: 99%
“…NSTI encompass a group of destructive soft tissue bacterial necrotic disease processes, which can involve skin, subcutaneous fat, fascia(s) and/or muscle(s), associated with rapid spread along tissue planes, systemic toxicity and potentiality for high mortality [11,12,[16][17][18][19][20][21][22].Although NSTIs have some common clinical features, various entities have been recognized, such as streptococcal gangrene, gas gangrene (clostridial myonecrosis), synergistic necrotizing cellulitis and progressive bacterial synergistic gangrene [5]. Subtle differences may distinguish one entity from another, but the clinical approach to diagnosis and treatment is similar.…”
Section: Nsti Disease: Overview and Current Conceptsmentioning
confidence: 99%
“…injure, scrape), where the organisms enter the soft tissue causing local infection, or (ii) occurring when a non-penetrating tissue injury (i.e. hematoma, muscle sprain) is infected by transient bacteremia, usually originating from the gastrointestinal or genitourinary tract [5,17,20,22,23]. A secondary infection by the host's own indigenous aerobic or anaerobic microflora usually leads to polymicrobial infection [4][5][6]14,16].…”
Section: Pathophysiology -Mechanisms Of Evolution Of the Diseasementioning
confidence: 99%
See 2 more Smart Citations